Konversi Nila Nipah (Nypa Fruticans Wurmb) Menjadi Bio Oil Dengan Teknologi Pirolisis Menggunakan Katalis Ni/Lempung - Muhammad Ismet; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fuel oil is a natural resource, due that needsare very important. Fuels are nonrenewable energy sources. Bio-oil is one of thealternative energy solutions that can be used as a subtitute for petroleum. Riau province has palm plantation area of 75459.26 Ha and is also rich in natural resources such as the potential of natural clay. Bio-oil can be produced from a palm frond by using pyrolisis process with catalyst Ni/clay. This study aimed to determine the effect of the catalyst Ni/clay variation toward the biomass, the influence of variations developing of metal toward clay and characterization of physical and chemical properties to the yield of bio-oil product. in this study the pyrolisis process carried out at a temperature of 320°C, 500 ml silinap, biomass 50 grams with the size of -100+200 mesh sieve and the variatio of catalyst Ni/clay by 0,4%, 0,5%, 0,6% w/w to the biomass and Ni metal carrier variation 0f 0%, 1%, 2%, 3% w/w of the clay. The research product bio-oil 72.072% of yields in 0,6% of catalyst and 1% of metal. The result of the analysis of physical properties of bio-oil obtained is the 0.924 gr/ml density, 2.351 cSt viscosity, acid number 70.218 mg NaOH/gr sample and 50°C flash point. Chemical properties analysis of bio-oil using GCMS (Gass Chromatography-Mass Spectroscopy) on the use of catalyst 0,6% and metal 1%obtained five dominant chemical compound that is 2-Methylpropene 2.84%, 2,4,4-Trimethyl-1-pentene 3.84%, 2,2,4,4-Tetramethylpentane 6.78%, cyclohexane,1bromo-4-methyl 8.13% and 2,4,4-Trimethyl-2-penten 5.11%.   Keyword: Bio-oil, pyrolysis, sheath Nipah, catalyst Ni / clay, Yield.